Study of β-Catenin Levels in sera and urine of Iraqi Women with Breast Carcinoma - Mahmoud, Hiba Qasim; Hamzah, Mohammed Imran; Ibrahim, Mazin Judy (Iraqi Journal of Science, 2025)
Breast cancer is a complex and multifaceted disease, comprising diverse subtypes that can be characterized by distinct histopathological, molecular, and clinical features. The dysregulation of β-catenin, a key transcription factor in the Wnt/β-catenin signaling pathway, plays a critical role in the early stages of tumorigenesis, ultimately influencing clinical outcomes. This study aimed to determine the correlation between sera and urine β-catenin levels in Iraqi patients with breast cancer comparing with control and first relative groups and to assess whether urine can be utilized as a substitute to sera to measure this status. The levels of β-catenin in fasting sera and urine were measured in a cohort of 29 breast cancer patients, as well as in 29 of their first-degree relatives and 30 age-matched healthy individuals serving as controls. All patients and first relatives were attending to the Oncology Teaching Hospital in Medical City. Sera and urine β-catenin concentration were measured using enzyme-linked immunosorbent assay. Urine creatinine concentrations were measured by colorimetric assay using automatically Roche/Hitachi cobas c111 System. Sera levels of β-catenin were significantly lower in breast cancer patients than in first relative and controls (p < 0.01). While in urine, levels of β-catenin were significantly higher (p <0.001) in breast cancer than in control and first relative groups. Low levels of β-Catenin in sera and high levels of this marker in urine of breast cancer patients comparing with control and first relative degree groups pointed out that β-catenin may serve as a diagnostic and prognostic biomarker, more studies needed to comfier these results.